Reproducible Digital Restoration of Fossils Using Blender - DeVries, Raina P.; Sereno, Paul C.; Vidal, Daniel; Baumgart, Stephanie L. (Frontiers in Earth Science, 2022)
Digital restoration of fossils based on computed tomographic (CT) imaging and other scanning technologies has become routine in paleontology. Digital restoration includes the retrodeformation and reconstruction of a fossil specimen, the former involving modification of the original 3D model to reverse post-mortem brittle and plastic deformation and the latter involving the infilling of fractures, addition of missing pieces, and smoothing of the mesh surface. The restoration process often involves digital editing of the specimen in ways that are difficult to document and reproduce. To record all actions taken during the digital restoration of a fossil, we outline a workflow that generates both the restored bone and the sequence of steps involved in its retrodeformation and reconstruction. Our method can also generate an animation showing the transformation of the original digital model into its final form. We applied this method to a dorsal rib and frontal bone of a small-bodied Jurassic-age armored dinosaur from Africa, the digital restoration of which engaged all modalities of deformation (translation, rotation, scaling, distortion) and reconstruction (fracture infilling, adding missing bone, surface smoothing). Each bone was CT-scanned, segmented, and imported into Blender, an open-source 3D-graphics animation program. Blender has an animation tool called an “armature” that allows for precise control over portions of a surface mesh while keeping a record of manipulations. To retrodeform a fossil, an armature is created and then linked, or “rigged,” to the fossil in order to control the displacement and distortion of its fragments. After using the armature to perform retrodeformation, we use Blender to record the movement and distortion of each fragment and also record reconstructive modifications. By ensuring documentation and reproducibility in an open-source program, our workflow and output open a window onto the heretofore largely hidden process of digital restoration in paleontology.